Reduction of the risk of cervical intraepithelial neoplasia in HIV-infected women treated with highly active antiretroviral therapy - Soncini, E.; Zoncada, A.; Condemi, et al., V. (Acta Biomedica Atenei Parmensis, 2007)
Background and aim of the work: The purpose of our study was to determine whether highly active antiretroviral therapy (HAART) reduces the onset of cervical intraepithelial neoplasia (CIN) in HIV-positive women. Methods: The study was designed to assess CIN incidence in a cohort of 101 HIV-positive women and to evaluate its relationship with ongoing antiretroviral therapy. The patients were screened through a combined Pap smear and colposcopic examination on a yearly basis. If any abnormalities were reported, the patients underwent targeted biopsy with histological confirmation of the diagnosis. Results:During the follow-up period, 38 patients (37.6%) developed histologically verified CIN, including low-grade CIN in seven patients (6.9%) and high-grade CIN in 31 patients (30.4%).Over the study period, 43 patients (42.6%) were treated with HAART for at least 6 months, the average duration of treatment being 37 months. Analysis of HAART efficacy in preventing CIN onset, determined by the Cox regression model with a time-dependent covariate adjusted for the CD4 level at the first visit, showed that HAART significantly reduced the risk of developing CIN (hazard ratio, 0.3; p = 0.004). Conclusion: HIV-positive patients present a high incidence of CIN and of high-grade CIN in particular. HAART exhibits a protective action against the onset of cervical lesions.